Proceedings of the the First International Conference on Islamic Development Studies 2019, ICIDS 2019, 10 September 2019, Banda 2019
DOI: 10.4108/eai.10-9-2019.2289386
|View full text |Cite
|
Sign up to set email alerts
|

Remuneration Of Employee Performance (Work Satisfaction and Motivation as a Variable of Mediation)

Abstract: This study aims to find empirical evidence of the effect of remuneration on employee performance in the public sector at the Raden Intan Lampung State Islamic University with job satisfaction and motivation as mediating variables. This study uses the SEM-PLS data analysis method with a sample of 53 lecturer respondents and 47 tendant respondents using the purposive judgment sampling method.The results showed that remuneration had a positive influence on motivation and job satisfaction of both lecturers and stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…This satisfaction was relative and subjective, which it was referred that every individual has satisfaction level and this satisfaction might be increased due to the individual need. Islam and Purnamasari (2019) in their article have explained another perspective which the researcher with economic psychology background argued that the practice of remuneration scheme relating to performance at a public sector could ruin individual performance when it was faced to job satisfaction. Moreover, the job satisfaction was also affected by other variables outside of remuneration.…”
Section: Moderation Of Job Satisfaction In the Effects Of Remuneratio...mentioning
confidence: 99%
“…This satisfaction was relative and subjective, which it was referred that every individual has satisfaction level and this satisfaction might be increased due to the individual need. Islam and Purnamasari (2019) in their article have explained another perspective which the researcher with economic psychology background argued that the practice of remuneration scheme relating to performance at a public sector could ruin individual performance when it was faced to job satisfaction. Moreover, the job satisfaction was also affected by other variables outside of remuneration.…”
Section: Moderation Of Job Satisfaction In the Effects Of Remuneratio...mentioning
confidence: 99%
“…Interestingly, while compensation was ranked highly in terms of its influence on job satisfaction, the mean satisfaction scores revealed that faculty members were relatively satisfied with their current packages. This apparent contradiction might reflect a subtle reality where faculty members, despite acknowledging their contentment with the existing packages, still consider improved compensation a priority for enhancing job satisfaction 23,24 . This indicates a broader context where even satisfactory aspects of employment are seen as areas for potential enhancement to achieve higher satisfaction levels.…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C ...mentioning
confidence: 99%
“…Performance cannot be achieved optimally if remuneration is not given proportionally (Davidescu et al, 2020;Simmonds et al, 2020). Remuneration is an employment benefit that can be in the form of salary, honorarium, fixed allowance, incentive, bonus or achievement, severance or pension (Islam and Purnamasari, 2019). According to the Rector Regulation of University of Padjadjaran Number 6 of 2020, performance incentives of the University of Padjadjaran are incentives given to lecturers as an appreciation for performance or contribution to University of Padjadjaran.…”
Section: Introductionmentioning
confidence: 99%